2022
DOI: 10.3390/genes13050736
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immune Status in Two Cohorts of Atlantic Salmon Raised in Different Aquaculture Systems (Case Study)

Abstract: Assessment of immune competence of farmed Atlantic salmon is especially important during smoltification and the first several months in the sea. Recently developed tools were applied to salmon raised in a traditional flow-through facility (FT, cohort 1) and in a recirculation aquaculture system (RAS, cohort 2). Fish were sampled at four time-points: parr, smolt, and at three weeks and three months after seawater transfer (SWT); expression of 85 selected immune and stress genes, IgM transcripts (Ig-seq), and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…45 genes with tissue specific regulation were selected from an established gene set composed of key immune and stress regulated genes in Atlantic salmon (Krasnov et al, 2020;Lund et al, 2022;Supplementary Table 4). We extended this set by three immunogene-specific primers derived for hamp, saa5 and sod1 (Supplementary Table 4).…”
Section: Gene Expression In Liver Spleen and Intestinementioning
confidence: 99%
“…45 genes with tissue specific regulation were selected from an established gene set composed of key immune and stress regulated genes in Atlantic salmon (Krasnov et al, 2020;Lund et al, 2022;Supplementary Table 4). We extended this set by three immunogene-specific primers derived for hamp, saa5 and sod1 (Supplementary Table 4).…”
Section: Gene Expression In Liver Spleen and Intestinementioning
confidence: 99%
“…However, these alterations in transcript levels were rather modest, possibly due to the transfer within the protected RAS environment with a lower pathogen pressure than the open marine environment. Due to different experimental setups, it is difficult to compare our results with other studies investigating freshwater to seawater transfer ( Johansson et al, 2016 ; Karlsen et al, 2018 ; Lund et al, 2022 ), but the general pattern of gene expression is similar.…”
Section: Discussionmentioning
confidence: 86%
“…Gene expression profiling allows the detection of both systemic and local immune responses in key immune organs. Recent studies on Atlantic salmon have revealed a variety of genes that can be used to assess the salmon’s immune status ( Krasnov et al, 2020 ; Lund et al, 2022 ). Accordingly, expression analysis of stress- and immune-related genes can complement traditional indicators such as growth performance, organ health and plasma indicators.…”
Section: Introductionmentioning
confidence: 99%